A review on process recording in behavioural ethics education - Lina Lafta Jassim (International Journal on Orange Technologies, 2020)
This paper introduces, illustrates and explores the use of process recording as a tool in behavioural ethics education. An overview of the nature and components of process recording as a pedagogical tool is provided. Potential challenges and benefits associated with its use are described. The particular relevance of process recording for behavioural ethics education is highlighted. Illustrative examples of ethics-related process records are discussed.